2009
DOI: 10.1093/treephys/tpn039
|View full text |Cite
|
Sign up to set email alerts
|

Bud burst timing in Picea abies seedlings as affected by temperature during dormancy induction and mild spells during chilling

Abstract: In trees adapted to cold climates, conditions during autumn and winter may influence the subsequent timing of bud burst and hence tree survival during early spring frosts. We tested the effects of two temperatures during dormancy induction and mild spells (MS) during chilling on the timing of bud burst in three Picea abies (L.) Karst. provenances (58-66 degrees N). One-year-old seedlings were induced to become dormant at temperatures of 12 or 21 degrees C applied during 9 weeks of short days (12-h photoperiod)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
3
21
2
2
Order By: Relevance
“…It should be noted that an extended growing season and autumn warming in the previous year could delay the onset of autumn syndrome stages (e.g., growth cessation, leaf fall, dormancy induction) and subsequently affect the phenology of the following spring in temperate and boreal trees [10], [38], [39]. In the current model, we assumed that the onset of dormancy takes place on Oct 1 of the previous year without explicitly accounting for the effects of autumn climate on dormancy induction.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that an extended growing season and autumn warming in the previous year could delay the onset of autumn syndrome stages (e.g., growth cessation, leaf fall, dormancy induction) and subsequently affect the phenology of the following spring in temperate and boreal trees [10], [38], [39]. In the current model, we assumed that the onset of dormancy takes place on Oct 1 of the previous year without explicitly accounting for the effects of autumn climate on dormancy induction.…”
Section: Discussionmentioning
confidence: 99%
“…2003; Søgaard et al . 2008; Granhus, Fløistad & Søgaard 2009). In Rosaceae species, dormancy is induced by the same temperature conditions, which also release the dormancy (Heide & Prestrud 2005; Heide 2008); in this instance, the response of the meristem to temperature changes during the endogenous development.…”
Section: Environmental Control Of the Dormancy Cycle In Budsmentioning
confidence: 99%
“…However, it has also been found that intermittent high temperature exposure may enhance the effects of chilling (Erez and Lavee 1971;Erez et al 1979a) and that the effect of intermittent high temperature exposure may depend on its timing (Hänninen and Pelkonen 1989;Young 1992;Granhus et al 2009) A review of studies addressing these complicated dynamics is outside the scope of the present volume, but the chilling negation observed in some of these experimental studies shows that unlike ontogenetic development, rest break is at least partially reversible. This has important implications for the modelling of rest break, as is shown in the next section.…”
Section: Experimental Studiesmentioning
confidence: 99%